2020
DOI: 10.1037/abn0000479
|View full text |Cite
|
Sign up to set email alerts
|

Participant carelessness and fraud: Consequences for clinical research and potential solutions.

Abstract: Clinical psychological research studies often require individuals with specific characteristics. The Internet can be used to recruit broadly, enabling the recruitment of rare groups such as people with specific psychological disorders. However, Internet-based research relies on participant self-report to determine eligibility, and thus, data quality depends on participant honesty. For those rare groups, even low levels of participant dishonesty can lead to a substantial proportion of fraudulent survey response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 52 publications
2
97
0
Order By: Relevance
“…Although MTurk operates an internal rating system of their workers, researchers are strongly advised to embed various attention and validity checks in their data collection tools to verify and ensure the quality of the collected data (Chandler, Shapiro, & Sisso, 2019; Dunn, Heggestad, Shanock, & Theilgard, 2018). Our own review of the methodological studies on MTurk revealed various types of data quality measures, including infrequency items (which have only one correct or highly probable answer), time measurements (with a minimum reading speed threshold), person-total correlations (capturing the subject’s internal consistency relative to the expected patterns derived from all other participants), long string analyses (which flags participants with a long string of identical answers), and exclusion of non-U.S. Internet protocol (IP) addresses and ones that are suspected to be indicative of automated activity.…”
Section: Existing Research On Depression Rates In Mturkmentioning
confidence: 99%
“…Although MTurk operates an internal rating system of their workers, researchers are strongly advised to embed various attention and validity checks in their data collection tools to verify and ensure the quality of the collected data (Chandler, Shapiro, & Sisso, 2019; Dunn, Heggestad, Shanock, & Theilgard, 2018). Our own review of the methodological studies on MTurk revealed various types of data quality measures, including infrequency items (which have only one correct or highly probable answer), time measurements (with a minimum reading speed threshold), person-total correlations (capturing the subject’s internal consistency relative to the expected patterns derived from all other participants), long string analyses (which flags participants with a long string of identical answers), and exclusion of non-U.S. Internet protocol (IP) addresses and ones that are suspected to be indicative of automated activity.…”
Section: Existing Research On Depression Rates In Mturkmentioning
confidence: 99%
“…The low compliance with open science recommendations found in our review, although it is in line with previous findings in psychology ( Vanpaemel et al., 2015 ) and psychiatry ( Sherry et al., 2020 ), showing that this practice is poorly followed by researchers, confirms that research related to the COVID-19 does not follow recommended measures to increase replicability of findings. Additionally, some warnings and recommendations have been made about the quality of internet-collected responses ( Chandler et al., 2020 ) and the practice of pre-analysis plans ( Olken, 2015 ) that apparently are not followed in the studies analysed.…”
Section: Discussionmentioning
confidence: 99%
“…This includes screenshots of human intelligence tasks (HITs), study eligibility criteria, embedded attention checks and survey links. Among all five intervention studies that our team has conducted on MTurk to date, we were able to find evidence of this information sharing on TurkOpticon, Reddit, MTurkCrowd, TurkView and mturkforum [7][8][9][10]. Therefore, it is recommended that researchers monitor these common websites regularly during recruitment.…”
Section: Declaration Of Interestsmentioning
confidence: 84%